New records of Hydropsychinae (Insecta: Trichoptera: Hydropsychidae) from Assam, India - Pandher, Manpreet Singh; Kaur, Simarjit; Parey, Sajad Hussain (Zootaxa, 2025)
Three species of Hydropsychinae are recorded for the first time from the geographic limits of India. Hydropsyche dolosa Banks 1939, Potamyia flavata (Banks 1934), and Potamyia renatae Malicky 1997 (all from Manas National Park, Assam—a World Heritage site) are re-illustrated, redescribed, and recorded for the first time from India.